PENDAMPINGAN PENGELOLAAN JURNAL ILMIAH BORNEO PHYSICAL EDUCATION JOURNAL PROGRAM STUDI PENDIDIKAN JASMANI FKIP UNMUL - Cahyono, Didik; Cahyaningrum, Gyta Krisdiana; Fauzi, Muhammad Sukron; Naheria, Naheria (Gapenas Publisher, 2025)
This community service program aims to provide assistance in the management of the Borneo Physical Education Journal (BPEJ) which is managed by the Physical Education Study Program of FKIP UNMUL. BPEJ has an important role as a forum for scientific publications for academics and researchers in the field of physical education. Through this assistance, it is hoped that the quality of journal management can improve, its visibility will be wider, and it will be able to contribute more optimally to the development of science in the field of physical education. This mentoring activity is carried out in several stages that are structured and comprehensive, namely through the stages of preparation, implementation, evaluation and follow-up, The results of post-test and data analysis show that BPEJ scientific journal management assistance activities have had a positive impact on journal management and publications. Increasing participants' understanding of journal management, increasing the number and quality of published articles, and increasing the visibility of journals are indicators of the success of this activity